Design and manufacturing of flume apparatus to investigate the failure mechanism of riverbanks. Issue 1 (1st January 2019) - Aldefae, Asad H.; Alkhafaji, Rusul A.; Shamkhi, Mohammed S.; Kumer, Haider Q.
Abstract: To improve the experimental activities in the field of hydraulic and Geotechnical engineering, flume apparatus was designed, manufactured, and tested in the laboratories of the faculty of engineering at Wasit University, Iraq. The flume apparatus was designed precisely based on the principles of physical modeling in order to achieve the simulation of natural rivers problems in terms of water entry to the flume in a realistic way that happens in natural rivers, and the possibility of controlling water discharge, which produce a good opportunity to study many hydraulic and Geotechnical problems in natural rivers and open channels. This paper presents the details of the manufacturing process of the flume apparatus as well as the result of preliminary test. The test was to study the failure mechanism in riverbank which showed a very good prediction of the failure mechanism types that observed. The circular failure and planar failure as well as the initial tension cracks that appeared during short term condition of streaming flow are inspected. It was concluded also that the failure of the river banks during the water flow in the flume in prototype scale is consistent with what had been observed in the model scale.